Changes in US household balance sheet behavior after the housing bust and Great Recession: Evidence from panel data - Daniel Cooper (Federal Reserve Bank of Boston, 2013)
This paper uses panel data through 2011 to examine evidence of shifts in household balance sheet behavior following the financial crisis and Great Recession. The paper considers evidence of balance sheet repair through debt repayment as well as changes in the composition of households' balance sheets and/or saving decisions to determine whether households' desire for holding or investing in riskier versus safer assets has changed. The data show relatively small and limited balance sheet adjustment - especially for those households considered the most likely to have been impacted by the economic collapse. The adjustment that did occur typically raised households' liquid asset holdings and/or saving and reduced their risky asset positions (stocks). There is also some evidence of increased nonhousing debt repayment and slower takeup of new nonhousing debt. Overall, the findings are inconsistent with major adjustments occurring in households' balance sheet behavior - especially to the extent where these shifts would have contributed substantially to the sluggish economic recovery.
Keywords: E21; D14; G11; 330